COMPARATIVE STUDY BETWEEN CONVENTIONAL VERSES UNDER VISION CLOSURE FOR LAPAROSCOPIC PORT SITE- PROSPECTIVE STUDY - Roshni Devi Patil; Girish Kullolli; Vikram Sindagikar; Tejaswini Vallabha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective. To study the comparison Between Conventional Versus Under Vision Closure For Laparoscopic Port Site-Prospective cross sectional interventional study Methods: All patients admitted in Department of Surgery Shri B.M.Patil Medical College, Hospital and Research centre, Vijayapur between September 2016 to August 2018. The patient will be divided under 2 groups-the first group will undergo closure conventionally and second under vision. Result: Total of 198 cases were considered out of which, the complications were tabulated and was seen that port site bleeding was seen in 5.1% in case and 7.1% in control, the p value was calculated to be 0.267. Port site infection was seen in 9.2% in case and 14.3% in control, the p value was calculated as 0.316. Port site hernia was seen in only 1 case in the control group, p value was found to be 0.551.Conclusion:  Port site complications are very minimally associated with laparoscopic surgeries. In our study we found only 1 case with herniation of small bowel. All the complications were managed with minimal intervention, and morbidity. Consideration of meticulous surgical technique during closure of the port can minimize these complications. There were 0.14% laparoscopic port site hernias, which is less. But designing a method for port closure, will reduce the incidence still further